2018
DOI: 10.1038/s41397-018-0045-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea in the management of sickle cell disease: pharmacogenomics and enzymatic metabolism

Abstract: Hydroxyurea (HU) was approved to be used in the treatment of sickle cell disease (SCD) because of its anti-sickling potential. However, there is variability in HU response among SCD patients and this can be due to physiological, socioeconomic, environmental, metabolic and/or genetic factors. The present review focuses on the latter two. Three quantitative trait loci, HBG2, BCL11A and HMIP, have been suggested as important markers for HU response. Other genes (ASS1, KLF10, HAO2, MAP3K5, PDE7B, TOX, NOS1, NOS2A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 63 publications
2
21
0
1
Order By: Relevance
“…The present study investigated the wider effect of HU on laboratory parameters in children with SCA, according to the presence of the β S haplotype and α-thalassemia. It has been reported that individuals with SCA taking HU may present an improved clinical profile before significant increases in HbF levels are seen, and it is known that HU response can vary according to β S haplotype and α-thalassemia [11,13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study investigated the wider effect of HU on laboratory parameters in children with SCA, according to the presence of the β S haplotype and α-thalassemia. It has been reported that individuals with SCA taking HU may present an improved clinical profile before significant increases in HbF levels are seen, and it is known that HU response can vary according to β S haplotype and α-thalassemia [11,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is believed that increases in HbF levels mediates HU efficacy among individuals with SCA, it was reported that improvement in patients’ clinical profiles appears prior to any significant increase in their HbF levels, suggesting that HU may modulate other laboratory parameters beside the classical increase seen in HbF [11]. Regarding HbF levels and the patient clinical profile, there is a great variability in response among individuals treated with HU, which may be due to genetic factors, including the β S -globin gene cluster haplotype [13,14]. Moreover, despite evidence demonstrating its efficacy, HU is underused in younger individuals with SCA due to a range of issues, mainly side effects, which have not been completely elucidated [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to therapy adherence, or socioeconomic, environmental, physiological and genetic factors. Nonetheless, genetic factors have been highlighted as one of the most important determinants of variation in HU therapeutic response ( Gravia et al, 2014 ; Yahouédéhou et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms in genes encoding drug-metabolizing enzymes (DME) and solute carriers may alter the bioavailability of drugs and metabolism, thereby influencing efficiency and toxicity ( Sheng et al, 2014 ). Accordingly, we recently conducted a review of the literature focused on genome-wide association studies that investigated genetic biomarkers effects on HU response and studies that investigated HU metabolism ( Yahouédéhou et al, 2018a ). Evidence showed the involvement of enzymes of the CYP450 family and catalase in HU metabolism, as well as the association between the urea transporter-B (UTB) and HU response in erythroid cells.…”
Section: Introductionmentioning
confidence: 99%
“…Este medicamento actúa a través de varios mecanismos que mejoran la disponibilidad de la HbF, con un descenso en la HbS, además, disminuye la expresión de moléculas de adhesión y la liberación del óxido nítrico mejorando los síntomas (36,37).…”
Section: Tratamientounclassified